Protocol for long-term treatment of lowly aggressive cancer cell lines with low concentrations of anti-tumor drugs - Ríos Medrano, Mayra Agustina (2024)
The understanding of anti-tumor drug effects requires specific experimental settings which model clinical scenarios. We describe a protocol for 10-day treatment of lowly aggressive tumor cell lines with antineoplastic agents at concentrations which do not affect cell growth. We describe steps for seeding cells and treating cells with anti-tumor drugs. We then detail steps for cell sensitivity, cell proliferation, and mRNA and protein expression assays. We also detail assays to determine modifications in compound efflux.